Welsh voluntary sector funding in the post-2010 austerity period - Nikos Kapitsinis (Welsh Economic Review (WER), 2021)
The paper examines the funding of Welsh voluntary sector organisations (VSOs), in terms of income source and type, in the aftermath of the 2007-08 global economic crisis, seeking to explore marketisation trends. A detailed examination of voluntary sector income from 2010-11, at the beginning of the austerity period, to 2016-17, the financial year with the latest available figures, provides valuable insights to both academic and policy inquiry about VSOs and their financial resilience. Several works have examined the voluntary sector funding in the aftermath of the 2007-08 economic crisis (Osborne, 2012; Clifford, 2017). Osborne (2012) indicated that Scottish charities reacted positively to the effects of the recession, with Scottish Government funding increases compensating for the decline in voluntary donations. Clifford (2017) showed that English and Welsh charities' income had significantly declined from 2008 to 2014. This paper provides some insights into how VSOs might respond to the current economic conditions affecting the Welsh economy.
Keywords: 330; Nonprofit-Organisation; Fundraising; Wales